Impact of Accounting Record-Keeping on the Sustainability of Small-Scale Enterprises in Kano Metropolis - Hamid, Kabir Tahir; Maigoshi, Zaharaddeen Salisu; Abdullahi, Zaharaddeen (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2023)
This study examined the impact of accounting record keeping on sustainability of small-scale enterprises (SSEs) in Kano metropolis. The population of this study comprised of all SSEs operating in the eight local government areas that constitute Kano metropolis. Four hundred and thirty-nine (439) questionnaires, using 5-point Likert scale, were administered on the sampled owners of SSEs across the eight local government areas in Kano metropolis. Out of this, four hundred and thirty-seven (437) questionnaires were completed and returned, while two respondents did not return their questionnaires. The statement on the questionnaire covers accounting record keeping, business performance, environmental attitude and community attitude. Structural equation modelling (SEM) analysis using Partial Least Square (PLS) was employed to analyze the data generated for the study. The finding of study shows that record keeping has a significant positive relationship with sustainability. This indicates that an increase in the record keeping behavior will lead to an increase in the sustainability of a business entity. The study, therefore, recommends that SMEs owners should learn basic record keeping knowledge or engage the service of bookkeepers to enable them to keep proper books of accounts which will in turn increase the sustainability of their businesses.